PENGARUH KECERDASAN EMOSIONAL, KARAKTERISTIK INDIVIDU DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN PINRANG - risman Umar; Mashur Razak; Saripuddin D (Nobel Management Review, 2020)
The study aims to determine and analyze the effect of partially and simultaneously motivation, individual characteristics, and work motivation on employee performance at the Pinrang District Secretariat, as well as the most dominant variable influencing employee performance at the Pinrang District Secretariat.This type of research is descriptive quantitative, while the nature of the research is descriptive explanatory research. The study was conducted at the Pinrang Regency Regional Secretariat. Implementation of research for 3 months. The population in this study amounted to 95 employees in the Pinrang District Secretariat. The sample in this study is the entire population taken as a sample. Thus the number of samples is equal to the population (census or saturated sample). So that a sample of 95employees at the Pinrang District Secretariat. Data analysis method used in this research is multiple linear regression model (multiple regression analysis). The results showed that there was a partial and simultaneous influence of emotional intelligence, individual characteristics and work motivation on the performance of the Pinrang District Secretariat staff, as well as the most dominant work motivation variable affecting the performance of the Pinrang District Secretariat staff.